Analisis Kapasitas Perikanan dengan Pendekatan Data Envelopment Analysis (DEA) di Perairan Utara Gorontalo - Olii, Abdul Hafidz (UI Scholars Hub, 2009)
Fishing capacity is ability of fishery input (boat) used in output production (catch), it measured by using fishing unit or other fishing gear production. In simple way, fishing capacity is an ability of fishing boat (with all aspects) to capture fish. This ability will depend on the fish stock to be captured (seasonally or yearly) and the ability of the fishing gear itself. The aims of this research are to analyze technical efficiency and capacity of capture fishery in between years, of fishing gear and of purse seine. Research location was in the northern water of Gorontalo. Data was analyzed using data envelopment analysis (DEA). The development of capture fishery in 20 years since 1986 - 2005 of the northern water of Gorontalo showed that 1995, 2003 and 2005 are the most efficient years compared to other years, therefore, these years can be used as a basic of allocating fishing effort and catch. The most efficient fishing gear was purse seine and line, whereas gill net is an inefficient fishing gear. For purse seine, there are 11 boats that have efficiency value of 1. In order to reach efficiency level of each purse seine, it needs to decrease the number of input such as reducing 27.97 percent of boat, reducing the length of fishing duration to 29.49 percent, reducing the length of fishing trip/tonnage month to 26.87 percent and reducing fishing operation cost to 15.67 percent.